2012
DOI: 10.4103/2230-8210.102999
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function tests in metabolic syndrome

Abstract: Objective:We evaluated the thyroid function tests in individuals with metabolic syndrome to explore the possibility of thyroid receptor resistance.Materials and Methods:The study was a cross-sectional study. It included 40 patients (group I) and 20 healthy individuals served as controls (group II). Patients in group I fulfilled the three or more of the NCEP ATP III (National Cholesterol Education Programme – Adult Treatment Panel III) criterion to define the metabolic syndrome. Blood sugar and serum insulin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
5
10
0
Order By: Relevance
“…Chugh K et al in a similar study reported high TSH levels in subjects with MetS and attributed the rise to thyroid receptor resistance, which may be a part of MetS. [15] There have been enough reports which support a correlation between TSH levels and components of MetS and thus substantiate our findings. Abdominal obesity is the major risk factor for the development of metabolic syndrome and in the assessment of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 81%
“…Chugh K et al in a similar study reported high TSH levels in subjects with MetS and attributed the rise to thyroid receptor resistance, which may be a part of MetS. [15] There have been enough reports which support a correlation between TSH levels and components of MetS and thus substantiate our findings. Abdominal obesity is the major risk factor for the development of metabolic syndrome and in the assessment of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 81%
“…This differs from findings by some authors working in different regions and with different races. Workers in India [ 5 , 16 ], Taiwan [ 19 ] and Korea [ 18 ], found a high prevalence of sub clinical hypothyroidism in people with metabolic syndrome. Heima et al [ 23 ] working in Amsterdam also found an association between higher TSH levels and metabolic syndrome in euthyroid subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a large Chinese case control study, all components of the metabolic syndrome were associated with systematically higher TSH levels (Lai et al) (70). In a study done by Chugh et al,(2012) evaluating the thyroid function tests in individuals with metabolic syndrome to explore the possibility of thyroid receptor resistance, a significant increase was found in TSH levels in patients as compared to controls, while T 3 and T 4 levels were comparable in patients and controls concluding that raised TSH in patients with metabolic syndrome independent of lowered T 3 and T 4 suggests it to be a part and parcel of this syndrome (71). Another study done by Meher et al, (2013) found that body mass index, waist circumference, mean systolic pressure, diastolic pressure, fasting blood sugar, total cholesterol, LDL-C, triglycerides, and TSH were significantly higher, and FT3, free thyroxine (FT4) and HDL-C were significantly lower in the metabolic syndrome patients compared to the control group concluding that there is a significant association between subclinical hypothyroidism and metabolic syndrome, and it highlights the importance of thyroid function tests in patients with metabolic syndrome.(64,72).…”
Section: Discussionmentioning
confidence: 99%